2015
DOI: 10.1038/srep08466
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B Administration Induces Hot Flushes in Women

Abstract: Neurokinin B (NKB) is a hypothalamic neuropeptide binding preferentially to the neurokinin 3 receptor. Expression of the gene encoding NKB is elevated in postmenopausal women. Furthermore, rodent studies suggest that NKB signalling may mediate menopausal hot flushes. However, the effects of NKB administration on hot flushes have not been investigated in humans. To address this, we performed a randomised, double-blinded, placebo-controlled, 2-way cross-over study. Ten healthy women were admitted to a temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 43 publications
2
58
0
2
Order By: Relevance
“…VMS, predominantly hot flushes and night sweats, are experienced by 70-80% of women during the perimenopause (Jayasena et al 2015) and a similar proportion of men undergoing ADT (Karling et al 1994, Sharifi et al 2005. Rapid estrogen withdrawal appears to mediate flushes in women via an increase in release of neurokinin B, and possibly other mediators, from the hypothalamus (Jayasena et al 2015).…”
Section: Effect Of Estradiol On Vasomotor Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…VMS, predominantly hot flushes and night sweats, are experienced by 70-80% of women during the perimenopause (Jayasena et al 2015) and a similar proportion of men undergoing ADT (Karling et al 1994, Sharifi et al 2005. Rapid estrogen withdrawal appears to mediate flushes in women via an increase in release of neurokinin B, and possibly other mediators, from the hypothalamus (Jayasena et al 2015).…”
Section: Effect Of Estradiol On Vasomotor Symptomsmentioning
confidence: 99%
“…Rapid estrogen withdrawal appears to mediate flushes in women via an increase in release of neurokinin B, and possibly other mediators, from the hypothalamus (Jayasena et al 2015). Neurokinin B acts on neurokinin 3 receptors in the hypothalamic median preoptic nucleus, to stimulate heat dissipation effectors such as cutaneous vasodilatation, diaphoresis and coldseeking behaviour (Rance et al 2013, Jayasena et al 2015. In perimenopausal and postmenopausal women, estrogen replacement is the most effective pharmaceutical strategy for mitigating hot flushes (Nelson 2004), although an oral neurokinin 3 receptor antagonist recently appears promising (Prague et al 2017).…”
Section: Effect Of Estradiol On Vasomotor Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a randomised, double-blind, placebocontrolled crossover study in healthy premenopausal women, peripheral infusion of NKB intravenously induced hot flushes that were typical in location, duration, and observed physiological change to those described by postmenopausal women. 20 Additionally, Crandall and colleagues 21 recently found that genetic variation in TACR3, which is the gene that encodes NK3R, might account for the variability in experience of hot flushes reported among women. Therefore, the finding that pharmacological blockade of NKB signalling with an oral NK3R antagonist can significantly improve hot flush symptoms independent of any hormonal effect fits entirely with this pre-existing data.…”
Section: Ear and Labyrinth Disordersmentioning
confidence: 99%
“…13 Furthermore, over the past 20 years, Rance and colleagues have contributed to a growing body of evidence in rodents, [14][15][16][17] primates, 18 and post-mortem studies in human beings 19 that the KNDy neurons, and in particular NKB and its receptor (NK3R), are implicated in the aetiology of the menopausal hot flush (summarised in a comprehensive review by Rance and colleagues 10 ). Two recent publications further implicate NKB and NK3R in menopausal flushing: in a randomised, double-blind, placebo-controlled, crossover study, peripheral infusion of NKB intravenously to healthy premenopausal women induced hot flushes that were typical in location and duration to those described by postmenopausal women, 20 and Crandall and colleagues 21 found that genetic variation in TACR3, which is the gene that encodes NK3R, might account for the variability in experience of hot flushes reported among menopausal women. Such data led us to hypothesise that NKB-NK3R signalling was an important mediator of menopausal flushing, and therefore pharmacological blockade of NK3R with an oral antagonist could be a novel therapeutic target without the need for increased oestrogen exposure.…”
Section: Introductionmentioning
confidence: 99%